Prevalence and characterization of Clostridioides difficile isolates from retail food products (vegetables and meats) in Japan - Usui, Masaru; Maruko, Aika; Harada, Michiko; Kawabata, Fumi; Sudo, Tsubasa; Noto, Sayo; Sato, Toyotaka; Shinagawa, Masaaki; Takahashi, Satoshi; Tamura, Yutaka (Anaerobe, 2020)
The present study aimed to elucidate the prevalence of Clostridioides difficile in Japanese retail food products. For this purpose, retail food samples (242 fresh vegetables and 266 retail meat samples: 89 chicken meat; 28 chicken liver; 200 pork meat; 24 pig liver; 127 beef meat) were collected from 14 supermarkets between 2015 and 2019. C. difficile was isolated from eight (3.3%) fresh vegetable, six (6.7%) chicken meat, one (3.6%) chicken liver, one (0.5%) pork meat, and two (1.6%) beef meat samples; it was not isolated from pig liver. Of these isolates, 35% were toxigenic. All isolates were typable by PCR ribotyping and were resolved into 12 PCR ribotypes. Among these isolates, ribotype 014, which is distributed worldwide including in Japanese clinical cases, was detected among vegetable isolates. Therefore, although the C. difficile contamination rate in Japanese retail foods was low, these sources can be contaminated and could transmit these bacteria to humans. •We clarified that C. difficile is prevalent in retail foods, in Japan.•There was a positive ratio of C. difficile in retail foods in Japan.•Ribotype 014 was found in some Japanese food products.•Therefore, we suggest efficiently washing vegetables and heating meats before eating.